2010
DOI: 10.1159/000321326
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Calbindin-D28k and Calretinin in the Spinal Cord of Lungfishes

Abstract: A common pattern of distribution of neurons and fibers containing the calcium-binding proteins calbindin-D28k (CB) and calretinin (CR) in the spinal cord of terrestrial vertebrates has been recently demonstrated. Lungfishes are considered the closest living relatives of tetrapods, but practically no experimental data exist on the organization of their spinal cord. By means of immunohistochemical techniques, the localization of CB and CR was investigated in the spinal cord of the African (Protopterus dolloi) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 112 publications
(128 reference statements)
4
5
0
Order By: Relevance
“…The lack of cross‐reactivity between the CB and CR antibodies in the present study was clear, because many cells were distinctly labeled for either CB or CR, and only a small portion of neurons was double labeled in the combined experiments. Similar observations were reported previously for the retina and spinal cord of these lungfish species (Morona, Northcutt, & González, ).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The lack of cross‐reactivity between the CB and CR antibodies in the present study was clear, because many cells were distinctly labeled for either CB or CR, and only a small portion of neurons was double labeled in the combined experiments. Similar observations were reported previously for the retina and spinal cord of these lungfish species (Morona, Northcutt, & González, ).…”
Section: Methodssupporting
confidence: 91%
“…The detailed distribution of CBir and CRir cell populations in the spinal cord of these lungfish species has been detailed in a previous report (Morona et al, ). Our new observations confirmed that study and corroborated the presence of separated cell populations, with some double labeled cells, in the dorsal and ventral horns.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The abundant CBir and CRir spinal cells revealed in Dermophis are distinctly distributed in the dorsal and ventral gray fields largely resembling the situation found in urodeles and lungfish [Morona and González, 2009;Morona et al, 2010]. Significantly, in anurans the distribution of CB and CR in the spinal cord includes a variety of cells with different localizations and morphologies in close resemblance with the distributions reported in amniotes [Morona and González, 2006a].…”
Section: Spinal Cordsupporting
confidence: 68%
“…Both proteins act as intracellular calcium buffers (Miller, 1995), neuromodulators (Schwaller et al, 2002), or calcium sensors (McCue et al, 2010), among other functions. Antibodies raised against these proteins have been widely used as neuronal markers to characterize neuronal populations or brain regions in tetrapods (mammals: García-Segura et al, 1984;Celio, 1990;S equier et al, 1990;Jacobowitz and Winsky, 1991;Resibois and Rogers, 1992;Andressen et al, 1993;birds: Roth et al, 1981;Rogers et al, 1990;Puelles et al, 1994;reptiles: D avila et al, 1997amphibians: Necchi et al, 1999;Mil an and Puelles, 2000;Gonz alez, 2008, 2009;Morona et al, 2011a) and fishes (lampreys: Pombal and Puelles, 1999;Megías et al, 2003;elasmobranchs: Rodríguez-Moldes et al, 1990a,b;Anad on et al, 2009;chondrosteans: Graña et al, 2012;holosteans: Northcutt, 2009;teleosts: Díaz-Regueira and Anad on, 2000;Castro et al, 2003Castro et al, , 2006aNorthcutt, 2009;lungfish: Gonz alez et al, 2010;Morona et al, 2010).…”
mentioning
confidence: 99%